1969
DOI: 10.1071/bi9690523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Boron Nutrition on Growth and Development of Subterranean Clover

Abstract: SummaryIn the early stages, boron deficiency had little effect on dry matter accumulation by the plant as a whole. Root growth, however, declined significantly and this was accompanied by an accumulation of dry matter in the leaves. At progressive stages of boron deficiency distribution of dry matter to new leaf tissue also became restricted. When plants already deficient in boron were transferred to solutions without boron, increases in dry weight of existing leaves were greater than for the corresponding pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…. Similar effects of B deficiency on the DM of young and old leaves have been observed previously in subterranean clover (Bouma, 1969). Apparently, when the B supply from the roots is exhausted, too little B is mobilized from the old leaves of soybean or subterranean clover to prevent B deficiency from developing -• ... in young leaves and meristems; old leaves remain B adequate and, with the elimination of other sinks, accumulate the products of their own photosynthesis.…”
Section: Response Of Plant Dry Matter To B Deficiency and Its Relatiosupporting
confidence: 72%
“…. Similar effects of B deficiency on the DM of young and old leaves have been observed previously in subterranean clover (Bouma, 1969). Apparently, when the B supply from the roots is exhausted, too little B is mobilized from the old leaves of soybean or subterranean clover to prevent B deficiency from developing -• ... in young leaves and meristems; old leaves remain B adequate and, with the elimination of other sinks, accumulate the products of their own photosynthesis.…”
Section: Response Of Plant Dry Matter To B Deficiency and Its Relatiosupporting
confidence: 72%
“…Leaf temperature was not affected significantly by different treatments. Marschner et al,' 1986;Bouma, 1969;Berger, 1962; reported that due to micronutrient deficiency and soil moisture stress in surface soil reduced root growth, reduced transpiration, photosynthesis rate and also mineralization and availability of nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…This increase of weight could be the result of increased axillary shoots as a result of apical meristem termination. Bouma (1969) studied the effect of growing subterranean clover (Trifolium subterraneum) initially with a half strength B solution (0.001, 0.002, 0.004, or 0.032 mgÁL -1 ) for 7 d and then each B concentration was doubled for the next 7 d. Seedlings were then transferred into another container with the same complete fertilizer solutions containing either 0, 0.002, 0.004, 0.008, or 0.064 mgÁL -1 B. While Bouma (1969) reported a greater trend of increased shoot dry weight as compared with root dry weight when B was withheld, there was not a corresponding increase in shoot dry weight overall.…”
Section: Discussionmentioning
confidence: 99%